Altered levels of neurobiological biomarkers at the interface of depression and gestational diabetes mellitus in Asian Indian women. (June 2022) - Thirumoorthy, C.; Deepa, M.; Srikumar, B.N.; Hannah, W.; Venkatesan, U.; Nikhil, P.J.; Hemavathy, S.; Binukumar, B.; Anjana, R.M.; Ram, Uma; Balasubramanyam, M.; Saravanan, P.; et al.
Abstract: Aim: Gestational diabetes mellitus (GDM) might predispose the mothers to depression. Studies have reported the role of biomarkers either in GDM or depression, but very few have examined them in GDM with depression. The present study profiled the circulating levels of brain-derived neurotrophic factor (BDNF), Beta Endorphin (BE) and nesfatin-1 in women with GDM (with and without depression). Methods: 160 pregnant women at 24–28 weeks of pregnancy (NGT/GDM with & without depression, n = 40 each) were randomly selected from the ongoing STRiDE (STratification of Risk of Diabetes in Early pregnancy) study. Depression score was derived using PHQ-9 questionnaire and ELISA was used to quantify the biomarkers. Results: Circulatory levels of BDNF, BE and nesfatin-1 were lower in GDM women with or without depression compared to NGT without depression, however, nesfatin-1 levels were higher in NGT with depression. Notably, GDM with depression had the lowest levels of BDNF and BE. Both BDNF and BE levels were negatively correlated with depression, 1 h and 2 h plasma glucose. Regression analysis confirmed that each standard deviation decreases in BDNF and BE were independently associated with higher odds of GDM with or without depression even after adjusting for potential confounders. Conclusion: Our study has identified altered levels of a panel of neurobiological biomarkers (BDNF/BE/nesfatin-1) in those with combined GDM and depression. BDNF/BE could be potential biomarkers to assess the higher risk of coexisting depression and GDM.